An introduction to the financial system: money and banking - Steiner, W.H.; Shapiro, Eli (New York: Henry Holt and Company, 1953)
This book treats all sectors of the financial system and not merely that of commercial banking. Emphasis is placed upon the general principles directing the flow of savings into real investment and upon the role of the various financial institutions in facilitating the saving investment process.
Include bibliographic Index
osc 11/05/2018
Loans
Keywords: Money